Haematological Parameters of Pregnant Kano Brown Does Vaccinated Against Peste Des Petits Ruminants in Nigeria - Orakpoghenor, Ochuko; Markus, Talatu P.; Adamu, Jibril; Kazeem, Haruna M.; Olaolu, Olushola S. (Journal of Hematology Research, 2020)
Peste des petits ruminants (PPR) is an endemic disease of small ruminants globally and, the disease controlled primarily by vaccination. The aim of this study was to determine the changes in haematological parameters of pregnant goats vaccinated against PPR. Ten pregnant female goats were obtained for the purpose of this study. The pregnant goats were at about the same stage of pregnancy, confirmed by ultrasonography. Vaccination using the Nigeria 75/1 PPR virus vaccine was done at first trimester of pregnancy. Protective antibodies against PPR were detected one week post-vaccination using competitive enzyme linked immunosorbent assay (c-ELISA). Blood samples were collected in sample bottles containing ethylenediaminetetraacetic acid (EDTA) before vaccination and at two weeks interval post-vaccination for ten weeks. Microhaematocrit and thin blood smear techniques were used for the haematological analyses. Haemoglobin concentration (Hb) was determined using the cyanmethaemoglobin method. Mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) were calculated. There was no statistically significant difference in all the haematological parameters before and after vaccination against PPR. In conclusion, the vaccination of apparently healthy pregnant goats against PPR produced no alteration in the haemogram.